Evaluation and management of adult acquired buried penis - Ho, Tammy S.; Gelman, Joel (Translational Andrology and Urology, 2018)
Adult acquired buried penis represents the clinical manifestation of a wide spectrum of pathology due to a variety of etiologies. It can be related to obesity, a laxity in connective tissue, lichen sclerosis (LS), complications from penile/scrotal enlargement surgery, scrotal lymphedema, or hidradenitis suppurativa (HS). Buried penis can be associated with poor cosmesis and hygiene, voiding dysfunction, and sexual dysfunction. Evaluation and management of buried penis largely depends on etiology and degree of affected tissue. It is an increasingly common problem seen by reconstructive urologists and here we present several frequently seen scenarios of buried penis and management options.